2013
DOI: 10.1103/physrevb.88.125312
|View full text |Cite
|
Sign up to set email alerts
|

Single-electron double quantum dot dipole-coupled to a single photonic mode

Abstract: We have realized a hybrid solid-state quantum device in which a single-electron semiconductor double quantum dot is dipole coupled to a superconducting microwave frequency transmission line resonator. The dipolar interaction between the two entities manifests itself via dispersive and dissipative effects observed as frequency shifts and linewidth broadenings of the photonic mode respectively. A Jaynes-Cummings Hamiltonian master equation calculation is used to model the combined system response and allows for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
90
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 39 publications
8
90
2
Order By: Relevance
“…Such large variation is unexpected. It is in direct contrast with the behavior observed in semiconductor QDs, where Basset et al [36] found that the dephasing rate in a GaAs DQD varies little between the few-electron and many-electron regimes, which suggests that charge number had only minor effect in that system. An intriguing observation in our experiment is that the dephasing rate not only varied significantly, but the pattern of the variation also appeared to repeat every four charges for the right dot.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…Such large variation is unexpected. It is in direct contrast with the behavior observed in semiconductor QDs, where Basset et al [36] found that the dephasing rate in a GaAs DQD varies little between the few-electron and many-electron regimes, which suggests that charge number had only minor effect in that system. An intriguing observation in our experiment is that the dephasing rate not only varied significantly, but the pattern of the variation also appeared to repeat every four charges for the right dot.…”
contrasting
confidence: 48%
“…To our knowledge, such periodic variation of a physical quantity has not been seen in any experiment on graphene QDs. Basset et al [36] found that the dephasing rate depends on 2t C for a fixed charge state; however, 2t C in our device is tuned to be around 6-8 GHz [22], which should not be seen as a main source of the observed periodicity. While the data fitting process may have an ∼ 20% error, which is mainly caused by the transformation of [21], the periodic variation is not affected.…”
mentioning
confidence: 99%
“…figure 18. Such hybrid structures that allow the investigation the interplay of light and matter at the nansocale have recently gained a lot of interest both theoretically [167,168,169,170,171,172,173,174,175,176,177] as well as experimentally [178,179,180,181,182,183,184,185,186] in the context of circuit quantum electrodynamics. Similar to the previously discussed energy harvester, the hybrid microwave cavity heat engine [57] also allows to separate the hot and the cold part of the engine by a macroscopic distance of the order of a centimeter.…”
Section: Microwave Cavity Photonsmentioning
confidence: 99%
“…But there are also several resonances visible for which β > 0 (diagonal lines), for example the ones denoted by the black arrow in figure 2 (b). A resonance with a positive slope can be explained as a transition between two states both localized in the channel and capacitively coupled to the gates similar to inter-dot transitions as observed in double quantum dots 6,25,26 , but a more likely explanation in this case are localized states in the gate. This is because for transitions between localized state inside the channel, the lines are expected to terminate (or at least change slope) when the overall charge state of the system changes.…”
mentioning
confidence: 99%
“…In devices similar to the ones in this work, we have observed ratio of the gate capacitance over the total capacitance up to ∼ 0.9. In a highly optimized structure with a superconducting strip-line resonator with a high loaded quality factor dispersive read-out of a double quantum dot has recently even proven to be superior to charge sensing using a quantum point contact 26 . However, here we focus on a setup using a chip inductor with an inherently low quality factor.…”
mentioning
confidence: 99%